Green Human Resource Management Behavior from a Maqashid al-Shariah Perspective: Evidence from the Inspectorate of Central Lampung Regency, Indonesia - Endrie Sanjaya; Finny Ligery; Ahmad Muklisin (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of Green Human Resource Management (GHRM), Religiosity, and Organizational Commitment on Employee Green Behavior. The study uses a quantitative approach with a survey method, where data is collected through a questionnaire to 55 employees as respondents. The research instrument has met the validity and reliability test (Cronbach's Alpha > 0.60), then the data is analyzed using multiple linear regression. The results of the analysis showed that simultaneously GHRM, religiosity, and organizational commitment had a significant effect on the green behavior of employees. GHRM partially has a positive and significant effect on the green behavior of employees, while Religiosity and Organizational Commitment have no significant effect. These findings confirm that improving employees' green behavior is more effective through strengthening GHRM practices, such as green training, environmentally friendly work policies, environmental-based performance evaluation, and reward systems